Fanatical prospecting the ultimate guide for starting sales conversations and filling the pipeline by leveraging social selling, telephone, email, and cold calling - Blount, Jeb (Wiley, 2015)
Explaining the why and how behind the most important activity in sales and business development--prospecting, this book offers a step-by-step, innovative approach to prospecting that works for real people, in the real world, with real prospects. --
Includes bibliographical references and index. - Print version record and CIP data provided by publisher
Keywords: Selling; Business referrals; Customer relations; Vente; Méthode de la boule de neige (Marketing); selling; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior